2014
DOI: 10.1093/jnci/dju050
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of TRIM44: Pairing a Prognostic Target With Potential Therapeutic Strategy

Abstract: BackgroundMany prognostic biomarkers have been proposed recently. However, there is a lack of therapeutic strategies exploiting novel prognostic biomarkers. We aimed to propose therapeutic options in patients with overexpression of TRIM44, a recently identified prognostic gene.MethodsGenomic and transcriptomic data of epithelial cancers (n = 1932), breast cancers (BCs; n = 1980) and esophago-gastric cancers (EGCs; n = 163) were used to identify genomic aberrations driving TRIM44 overexpression. The driver gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…Accumulating evidence indicates that the activation of the AKT/mTOR pathway plays a key role in controlling fundamental cellular processes, including cell growth, proliferation, apoptosis and metabolism in different cancer types . A previous study showed a statistically significant correlation between TRIM44 and the mTOR signaling pathway in EGC . The TRIM44‐overexpression gene signature of EGC was reversed by AKT/mTOR pathway inhibitors .…”
Section: Discussionmentioning
confidence: 93%
“…Accumulating evidence indicates that the activation of the AKT/mTOR pathway plays a key role in controlling fundamental cellular processes, including cell growth, proliferation, apoptosis and metabolism in different cancer types . A previous study showed a statistically significant correlation between TRIM44 and the mTOR signaling pathway in EGC . The TRIM44‐overexpression gene signature of EGC was reversed by AKT/mTOR pathway inhibitors .…”
Section: Discussionmentioning
confidence: 93%
“…Accumulating studies have shown that TRIM family proteins may positively or negatively regulate carcinogenesis depending on the types of TRIM or the origin of cancer . Specifically, TRIM44 has been reported in a number of studies showing oncogenic effect in various cancers . Ong et al have reported that TRIM44 overexpression resulted from genomic amplification in 16.1% of all epithelial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Specifically, TRIM44 has been reported in a number of studies showing oncogenic effect in various cancers. [17][18][19][20][21][22][23][24][25][26] Ong et al 20 have reported that TRIM44 overexpression resulted from genomic amplification in 16.1% of all epithelial cancers. From a clinicopathological point of view, we previously showed that TRIM44 overexpression was associated with poor prognosis in testicular germ cell tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations